Una nueva especie de Liotyphlops Peters, 1881 (Serpentes, Scolecophidia, Anomalepidae) del sur de la Amazonía Colombiana - Juan J. Silva Haad; Francisco Luís Franco; Jairo Maldonado (Biota Colombiana, 2008)
Silva Haad, J.J., Franco, F.L. and Maldonado, J. we described a new species of Liotyphlops Peters, 1881 (Serpentes, Scolecophidia, Anomalepidae), from southern Colombian Amazon, in the Amazonas department, one captured in the middle region of the Caquetá River, Vereda de los Ingleses, La Pedrera district; and another in vereda Los Lagos, Leticia municipality. It species is characterized by having reduction in the number of scales in the first and second row of lateral side of the head (three scales including the last supralabial), 384 dorsal scales, 20-20-20 dorsal scale rows, dorsal coloration light brown or beige, ventral region with yellowish stripe extending from gular region to the tail.